High-conductivity strain-insensitive elastic fiber and preparation and application thereof
By preparing conductive fibers with helical layered structures, the problem of the existing stretchable conductive fibers rising resistance under mechanical deformation is solved, and high conductivity and strain insensitivity are achieved, which is suitable for flexible wearable devices.
Patent Information
- Application Number
- CN202411850651.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-16
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2044-12-16
AI Technical Summary
The current stretchable conductive fibers have a sharp increase in the resistance of mechanical deformation, making it difficult to have high conductivity, strain insensitivity and stability, limiting their application in flexible wearable devices.
Using conductive fibers with a spiral layered structure, polymer elastomer porous fiber membranes are prepared by electrospinning, and liquid metal composites are scraped on their surface to form winding fibers with raised structures, and the liquid metal composites are embedded in the pores of the fiber membrane as an adhesive layer.
It achieves high conductivity (conductivity 1.5×106S/m) and strain insensitivity, has good structural stability, adapts to a variety of deformations, and is more reliable and durable in applications.
Smart Images

Figure CN119736789A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of functional materials, and particularly relates to a highly conductive and strain-insensitive elastic fiber and a preparation method and application thereof. Background Art
[0002] With the rapid development of flexible wearable technology, fiber-shaped stretchable devices are widely used in wearable sensors, soft robots, human-machine interfaces, and flexible energy storage and collection devices. Flexible and stretchable conductive fibers have the characteristics of miniaturization, high flexibility, and easy weaving and integration, and have been widely studied as an important component of wearable electronic systems. Compared with the limitation that traditional metal wires cannot be stretched and deformed, stretchable conductive fibers can provide continuous conductivity for electronic devices under mechanical deformation such as stretching and bending. The electrical properties of most stretchable conductive fibers are usually strain-sensitive, because the conductive material separates under mechanical deformation, causing a sharp increase in resistance. The electrodes or connecting wires of flexible wearable devices require the conductive fibers to have high conductivity and stable conductivity to ensure that the flexible devices can stably transmit electrical signals during mechanical deformation.
[0003] At present, most of the one-dimensional strain-insensitive conductive fibers are of skin-core structure, with the skin layer being a conductive material and the core layer being an elastic fiber. By designing the geometric structure of the conductive layer, such as the folds and spiral structures, the stability of the conductivity of the fiber under strain can be ensured. For example, Liu et al. wrapped a carbon nanotube layer on a pre-stretched rubber core fiber to prepare a strain-insensitive conductive fiber with a folded structure, and the conductivity of the fiber was 360S / m (Science 2015,349,6246). CN 113062116 B discloses a strain-insensitive conductive fiber with a bionic structure, wherein the conductive coating has a folded structure and the conductivity of the fiber is 10 -1 -10 2 However, the conductive materials used in these geometrically structured stretchable fibers are limited to carbon nanomaterials and conductive polymers, resulting in relatively low electrical conductivities, typically less than 10 4 S / m, and conductive materials are usually exposed to the environment, which seriously limits the widespread application of conductive fibers in the field of flexible wearables.
[0004] Recently, gallium-indium alloy (EGaIn) liquid metal has been widely used due to its metallic conductivity (conductivity: 3.4×10 6 S / m), liquid fluidity, and excellent biocompatibility. However, large volumes of liquid metal aggregates are prone to leakage under complex mechanical deformation, causing damage to the device circuit, which poses a challenge to its practical application in the field of flexible wearables. Therefore, it is very important to invent a stretchable conductive fiber with excellent conductivity, strain insensitivity, stability and durability in the field of flexible wearables. Summary of the invention
[0005] In view of the defects of the prior art, the technical problem to be solved by the present invention is to provide a highly conductive and strain-insensitive elastic fiber and its preparation and application, so as to overcome the defects of the current stretchable conductive fibers that are difficult to achieve strain insensitivity, high conductivity and stability.
[0006] The present invention provides a conductive fiber, which has a spiral layered structure; wherein the spiral layered structure comprises a fiber membrane layer and a liquid metal composite.
[0007] Preferably, the liquid metal composite is embedded between the fiber membrane layers and has a convex structure;
[0008] Preferably, the material of the fiber membrane layer is a polymer elastomer; the polymer elastomer is one or more of thermoplastic polyurethane TPU, styrene-butadiene-styrene block copolymer SBS, and hydrogenated styrene-butadiene block copolymer SEBS.
[0009] Preferably, the liquid metal composite comprises metal powder and gallium-indium alloy, further such as copper-gallium-indium alloy (Cu-EGaIn).
[0010] Furthermore, the conductive fiber comprises an elastic porous fiber membrane layer 1 and a liquid metal composite layer 2, wherein the liquid metal composite is loaded on the surface of the porous fiber membrane by blade coating and is formed into fibers by winding.
[0011] The present invention provides a method for preparing a conductive fiber, comprising:
[0012] The liquid metal complex is loaded on the surface of a porous fiber membrane and wound into fibers to obtain conductive fibers, that is, strain-insensitive, stretchable and highly conductive fibers.
[0013] Preferably, the liquid metal composite comprises metal powder and gallium-indium alloy; and the porous fiber membrane is a porous fiber membrane of a polymer elastomer.
[0014] Preferably, the mass ratio of the metal powder to the gallium-indium alloy in the liquid metal composite is 0.5-2:10; the metal powder is one or more of copper, iron and silver;
[0015] Furthermore, the average particle size of the metal powder is 0.5-15 μm.
[0016] Preferably, the mass percentage of gallium in the gallium-indium alloy is 75-85%, and the mass percentage of indium is 15-25%.
[0017] Furthermore, the metal and the gallium-indium alloy are obtained by mixing the metal and the gallium-indium alloy and shaking in a homogenizer; wherein the shaking time is 2-5 hours.
[0018] Preferably, the polymer elastomer is one or more of thermoplastic polyurethane TPU, styrene-butadiene-styrene block copolymer SBS, and hydrogenated styrene-butadiene block copolymer SEBS.
[0019] Furthermore, the porous fiber membrane of the polymer elastomer is an electrostatically spun porous fiber membrane.
[0020] Preferably, the method for preparing the porous fiber membrane of the polymer elastomer comprises: preparing a spinning solution with the polymer elastomer and an organic solvent, and performing electrospinning to obtain the porous fiber membrane.
[0021] Preferably, the organic solvent includes one or more of N,N-dimethylformamide DMF, tetrahydrofuran THF, dimethyl sulfoxide DMSO, 1,2-dichloroethane DCE, chloroform and toluene.
[0022] Preferably, the concentration of the spinning solution is 10-25% w / v.
[0023] Furthermore, the organic solvent for TPU is one or more of N,N-dimethylformamide (DMF), tetrahydrofuran (THF), and dimethyl sulfoxide (DMSO), and the ratio of TPU to the organic solvent is 15-25% w / v.
[0024] Furthermore, the organic solvent for SBS is one or more of 1,2-dichloroethane (DCE), DMF, and THF, and the ratio of SBS to the organic solvent is 10-20% w / v.
[0025] Furthermore, the organic solvent for SEBS is one or more of chloroform, toluene, and THF, and the ratio of SEBS to the organic solvent is 10-20% w / v.
[0026] The above w / v are all g / ml.
[0027] Preferably, the spinning solution is prepared by stirring the polymer elastomer and the solvent at room temperature or in an oil bath for 1-6 hours, and then standing at room temperature to obtain the spinning solution. Furthermore, the oil bath temperature is 60-80°C; the stirring rate is 300-500r / min; and the spinning solution is standing at room temperature for 12-24 hours to eliminate bubbles.
[0028] Preferably, the electrospinning process parameters are as follows: the distance between the electrospinning needle and the drum collector is 15-20 cm, the drum speed is 50-300 r / min, the needle movement speed is 5-20 mm / s, the solution extrusion speed is 1-4 ml / h; the positive and negative voltages are 10-15 kV and 1-5 kV respectively. The ambient temperature of the electrospinning process is controlled at 25-35°C, and the relative humidity is controlled at 30-40%.
[0029] Preferably, the loading method is scraping;
[0030] The winding is to use the liquid metal composite surface as the inner layer and wind it into fibers along the long sides;
[0031] The size of the porous fiber membrane is a rectangular fiber membrane with a length of 2-1000 mm and a width of 2-100 mm.
[0032] The thickness of the porous fiber membrane is 20-150 μm.
[0033] Preferably, the loading amount of the liquid metal complex to the area of the fiber membrane is 1.5-3 mg / cm 2 .
[0034] The present invention provides an application of the conductive fiber in the field of flexible wearable electronics, for example: a stretchable signal transmission line, a stretchable mobile phone charging line, and a stretchable Joule heating fiber.
[0035] The conductive fiber of the present invention is a spiral layered structure, including an elastic porous fiber membrane and a liquid metal composite material. The preparation method includes electrospinning an elastic porous fiber membrane, coating the liquid metal composite on the fiber membrane, and making the fiber through a winding process. The liquid metal composite is embedded in the pores of the interlayer fiber membrane, so that a strong bond is formed between the wound fiber layers, thereby ensuring the stability of the fiber structure. In addition, the liquid metal composite embedded in the pores of the fiber membrane has a protruding structure, which increases the effective conductive volume when strained, so that the conductive fiber has a strain-insensitive property. The fiber prepared by the present invention has a high electrical conductivity, and the conductive property is insensitive to mechanical strain, and has good application prospects in the field of flexible wearables.
[0036] Beneficial Effects
[0037] (1) The conductive fiber provided by the present invention has a self-packaging property. The liquid metal composite between the layers is not easy to leak. Moreover, the liquid metal composite embedded in the fiber membrane layer serves as an adhesive layer to make the conductive fiber self-supporting, thereby ensuring the stability of the conductive fiber structure. The conductive fiber can adapt to various deformations and is more reliable and durable in actual application scenarios.
[0038] (2) The conductive fiber liquid metal composite layer provided by the present invention has a large surface area and is a continuous phase, retaining its excellent electrical properties, so that the fiber can reach a high conductivity of 1.5×10 6 S / m.
[0039] (3) The conductive fiber liquid metal composite layer provided by the present invention has a protruding microstructure embedded in the fiber membrane pores. This protrusion increases the effective conductive volume when strained, making the conductive fiber strain-insensitive. BRIEF DESCRIPTION OF THE DRAWINGS
[0040] Figure 1 Schematic diagram of the structure of the conductive fiber of the present invention, wherein 1 is an elastic porous fiber layer, and 2 is a liquid metal composite layer;
[0041] Figure 2 is a flow chart of the preparation of the conductive fiber of the present invention;
[0042] Figure 3 The fiber surface (a) and the surface interface (b) obtained in Example 1 are scanning electron microscope images;
[0043] Figure 4 (a) is a cross-sectional view of the fiber obtained in Example 1, and (b) is a scanning electron microscope image of a local magnification;
[0044] Figure 5 The strain-resistance change of the fiber and Pouillet's theoretical liquid metal composite obtained in Example 1;
[0045] Figure 6 The stability of the resistance of the fiber obtained in Example 1 at 100% strain for 2000 cycles;
[0046] Figure 7 The change of the resistance of the fiber obtained in Example 1 under a pressure of 0-30N;
[0047] Figure 8 The surface scanning electron microscope image (a) and the enlarged image (b) of the interface of the fiber obtained in Example 1 under 100% strain;
[0048] Fig. 9 The surface scanning electron microscope image (a) and the enlarged image (b) of the interface of the fiber obtained in Example 1 after 5N, 50 cycles of pressure load. DETAILED DESCRIPTION
[0049] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.
[0050] TPU was purchased from BASF, model Elastollan 1185A; THF and DMF were purchased from Sinopharm Chemical Reagent Co., Ltd.; EGaIn was purchased from Shenyang Jiabei Trading Co., Ltd.
[0051] Example 1
[0052] The preparation process of conductive fibers is as follows: Figure 2 As shown, the specific steps are as follows:
[0053] Preparation of TPU fiber membrane: TPU particles were added to a mixed solvent of THF and DMF (volume ratio of 1:1) at a concentration of 25% w / v, magnetically stirred at 60°C for 4 hours to dissolve the TPU particles, and then allowed to stand at room temperature for 12 hours to obtain a uniform solution. The TPU solution was transferred to a 20ml syringe and connected with a 19G metal needle. The distance between the needle and the collector was 15cm, the movement speed of the needle was 10mm / s, and the extrusion speed of the solution was 3ml / h. The positive and negative voltages were set to 12kV and 1kV, respectively. The ambient temperature of the electrospinning process was controlled at 30±2°C, and the relative humidity was controlled at 35±5%. The drum collected the TPU porous fiber membrane on aluminum foil at a speed of 100r / min.
[0054] Preparation of Cu-EGaIn: Copper powder (average particle size 5.7 μm) was added to EGaIn (75% Ga, 25% In) in a mass ratio of 7:100 and shaken in a homogenizer for 3 h to obtain a uniform Cu-EGaIn liquid metal composite.
[0055] Preparation of conductive fiber: The fiber membrane with a thickness of 70 μm was cut into a rectangular shape with a length of 3 cm and a width of 1 cm. The liquid metal complex was loaded on the surface of the fiber membrane by blade coating, and the loading amount was 3 mg / cm 2 , with the liquid metal composite surface as the inner layer, wound along the long side to form a conductive fiber.
[0056] The morphology of the conductive fiber of this embodiment was characterized, as shown in FIG. Figure 3 As shown in Figure 2, the fiber morphology is uniform and there is no liquid metal composite seepage at the interface. Figure 4The cross-sectional morphology of the conductive fiber is shown. The diameter of the fiber is 823 μm and the cross-sectional shape of the fiber presents a spiral layered structure. This structure allows the presence of a large area of liquid metal composites. From the enlarged image, it can be seen that the liquid metal composite is embedded between the fiber membrane layer and has a protruding structure.
[0057] The strain stability of the conductive fiber of this embodiment is characterized by applying tensile strain to the fiber using a universal tensile testing machine at a displacement speed of 60 mm / min. At the same time, copper wires are connected to a digital source meter at both ends of the fiber to test its resistance change (the copper wire resistance is tested before the test and deducted after the test to avoid the influence of the lead resistance). Figure 5 As shown in the figure, the resistance of the conductive fiber is stable under strain, and the relative resistance change (ΔR / R0) is small. Under 100% strain, the relative resistance change is 0.16, while the theoretical resistance change of liquid metal predicted by the law is 3 under 100% strain. The resistance stability of the conductive fiber proposed in the present invention is much higher than the theoretical value. The fiber is subjected to strain cycles using a universal tensile testing machine, and its resistance change is tested at the same time. The fiber has a stable resistance for 2000 cycles under 0-100% strain, indicating that the fiber has good durability ( Figure 6 ). Use a cylinder with a diameter of 5 mm to apply pressure to the middle part of the fiber, such as Figure 7 The resistance of the conductive fiber increased by only 0.12Ω under a 30N pressure load, indicating that the fiber resistance is also insensitive to compressive strain. Figure 8 It shows that when the fiber is under 100% tensile strain, the liquid metal composite will not seep out to the fiber surface. After cyclic pressure load, there is no obvious liquid metal composite seepage at the interface because the fiber membrane has enough pores to accommodate the deformation of the liquid metal composite, which further demonstrates the stability and durability of the fiber. The conductivity of the fiber is 1.5×10 6 S / m.
[0058] Example 2
[0059] The preparation of the porous fiber membrane and the liquid metal composite was the same as in Example 1. The only difference was that for the preparation of the conductive fiber, the fiber membrane was cut into a rectangular shape with a width of 1 cm, and the liquid metal composite was loaded on the fiber membrane surface by blade coating, with a loading amount of 1.5 mg / cm 2 The liquid metal composite surface is used as the inner layer and wound along the long side to form a conductive fiber. The conductivity of the fiber is 0.9×10 6 S / m, the relative resistance change of the fiber under 100% strain is 0.37.
[0060] Example 3
[0061] The preparation of the porous fiber membrane and the liquid metal composite was the same as in Example 1. The only difference was that for the preparation of the conductive fiber, the fiber membrane was cut into a rectangular shape with a width of 0.3 cm, and the liquid metal composite was loaded on the fiber membrane surface by blade coating, with a loading of 3 mg / cm 2 The liquid metal composite surface is used as the inner layer and wound along the long side to form a conductive fiber. The diameter of the fiber is 469μm and the conductivity of the fiber is 1.5×10 6 S / m, the relative resistance change of the fiber under 100% strain is 0.15.
[0062] Comparative Example 1
[0063] Compared with the TPU / liquid metal composite coaxial structure fiber, TPU particles were added to DMF solvent at a concentration of 25% w / v, magnetically stirred at 60°C for 4h to dissolve the TPU particles, and allowed to stand at room temperature for 12h to obtain a uniform solution. Wet spinning was performed using a 19 / 23G coaxial metal needle, the coagulation bath was deionized water, the outer spinning solution was TPU solution, and the inner layer was deionized water, extruded at a speed of 0.3ml / min, and after fiber formation, it was soaked in deionized water for 8h, taken out and dried to obtain a one-dimensional hollow TPU fiber, and a copper-gallium-indium alloy liquid metal composite (copper-gallium-indium alloy liquid metal composite was the same as in Example 1) was injected into the hollow TPU fiber, and copper wire electrodes were connected at both ends and then encapsulated with epoxy resin. The strain-resistance change was tested, and the resistance change of the TPU / liquid metal composite coaxial fiber under 100% strain was 2.9, which was 18 times that of Example 1, indicating that the electrical stability of the conductive fiber proposed in the present invention is much higher than that of the coaxial structure liquid metal composite composite conductive fiber.
Claims
1. A conductive fiber, characterized in that: The fiber has a spiral layered structure; wherein the spiral layered structure comprises a fiber membrane layer and a liquid metal composite.
2. The conductive fiber according to claim 1, characterized in that: The liquid metal composite is embedded between the fiber membrane layers and has a convex structure; The material of the fiber membrane layer is a polymer elastomer; The liquid metal composite includes metal powder and gallium-indium alloy.
3. A method for preparing a conductive fiber, comprising: The liquid metal complex is loaded on the surface of the porous fiber membrane and wound into fibers to obtain conductive fibers.
4. The preparation method according to claim 3, characterized in that: The liquid metal composite comprises metal powder and gallium-indium alloy; the porous fiber membrane is a porous fiber membrane of polymer elastomer.
5. The preparation method according to claim 4, characterized in that: The mass ratio of the metal powder to the gallium-indium alloy in the liquid metal composite is 0.5-2:10; the metal powder is one or more of copper, silver, and iron; wherein the average particle size of the metal is 0.5-15 μm; The mass percentage of gallium in the gallium-indium alloy is 75-85%, and the mass percentage of indium is 15-25%; The polymer elastomer is one or more of thermoplastic polyurethane TPU, styrene-butadiene-styrene block copolymer SBS, and hydrogenated styrene-butadiene block copolymer SEBS.
6. The preparation method according to claim 4, characterized in that: The method for preparing the porous fiber membrane of the polymer elastomer comprises: preparing a spinning solution with the polymer elastomer and an organic solvent, and performing electrostatic spinning to obtain the porous fiber membrane.
7. The preparation method according to claim 6, characterized in that: The organic solvent includes one or more of N,N-dimethylformamide DMF, tetrahydrofuran THF, dimethyl sulfoxide DMSO, 1,2-dichloroethane DCE, chloroform, and toluene; the concentration of the spinning solution is 10-25% w / v; The spinning solution is prepared by stirring the polymer elastomer and the solvent at room temperature or in an oil bath for 1-6 hours, and then standing at room temperature to obtain the spinning solution; The electrospinning process parameters are as follows: the distance between the electrospinning needle and the roller collector is 15-20 cm, the rotation speed of the roller is 50-300 r / min, the movement speed of the needle is 5-20 mm / s, and the solution extrusion speed is 1-4 ml / h; the positive and negative voltages are 10-15 kV and 1-5 kV respectively; the ambient temperature of the electrospinning process is controlled at 25-35° C., and the relative humidity is controlled at 30-40%.
8. The preparation method according to claim 3, characterized in that: The loading method is scraping; The winding is to use the liquid metal composite surface as the inner layer and wind it into fibers along the long sides; The thickness of the porous fiber membrane is 20-150 μm.
9. The preparation method according to claim 3, characterized in that: The liquid metal composite loading is 1.5-3 mg / cm2 for the area of the fiber membrane. 2 .
10. Use of the conductive fiber according to claim 1 in the field of flexible wearable electronics.
Citation Information
Patent Citations
A biomimetic strain-insensitive conductive fiber and its preparation method
CN113062116B
Flexible stretchable electronic fiber membrane material and preparation method thereof
CN113818236A
Flexible stretchable electronic fiber membrane material with Janus structure and preparation
CN115341385A
Stretchable conductive fiber and preparation method thereof
CN116289186A
Conductive fiber with resistance insensitive to tensile strain and preparation method thereof
CN116516521A
Cited By
Anti-strain interference fiber with rattan whisker imitating structure and preparation method of anti-strain interference fiber
CN120575361A
A strain interference resistant fiber with a mimic whisker structure and a method of making the same
CN120575361B